2015
DOI: 10.1186/s13039-015-0148-1
|View full text |Cite
|
Sign up to set email alerts
|

Language impairment in a case of a complex chromosomal rearrangement with a breakpoint downstream of FOXP2

Abstract: BackgroundWe report on a young female, who presents with a severe speech and language disorder and a balanced de novo complex chromosomal rearrangement, likely to have resulted from a chromosome 7 pericentromeric inversion, followed by a chromosome 7 and 11 translocation.ResultsUsing molecular cytogenetics, we mapped the four breakpoints to 7p21.1-15.3 (chromosome position: 20,954,043-21,001,537, hg19), 7q31 (chromosome position: 114,528,369-114,556,605, hg19), 7q21.3 (chromosome position: 93,884,065-93,933,45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 25 publications
3
48
0
Order By: Relevance
“…Our findings in a neuronal cell line give support to the view that the breakpoint in our proband which separated these two functional enhancers may have altered the expression levels of both FOXP2 and MDFIC contributing to the observed speech and language deficits (Moralli et al 2015). Accordingly, we expect the expression of FOXP2 to be downregulated and the expression of MDFIC to be upregulated because of the displacement of both enhancers with respect to both genes (whereas FOXP2-E distal and MDFIC remained in chromosome 7, FOXP2-E proximal and FOXP2 were rearranged to chromosome 11).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Our findings in a neuronal cell line give support to the view that the breakpoint in our proband which separated these two functional enhancers may have altered the expression levels of both FOXP2 and MDFIC contributing to the observed speech and language deficits (Moralli et al 2015). Accordingly, we expect the expression of FOXP2 to be downregulated and the expression of MDFIC to be upregulated because of the displacement of both enhancers with respect to both genes (whereas FOXP2-E distal and MDFIC remained in chromosome 7, FOXP2-E proximal and FOXP2 were rearranged to chromosome 11).…”
Section: Discussionsupporting
confidence: 83%
“…Our findings in a human neuronal cell line give support to the view that the breakpoint in our proband, which separated each of these two intergenic enhancers from each other and consequently from one of the two genes they regulate, may have altered the expression levels of both FOXP2 and MDFIC contributing to the observed speech and language deficits (Moralli et al 2015). Whereas MDFIC remained in chromosome 7q with, predictably, FOXP2-E distal , FOXP2 was rearranged to chromosome 11p with, predictably, FOXP2-E proximal .…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…A recent study reported that lncRNA8975-1 (TCONS_00013888) was disrupted in severe speech and language disorders [20]. Our group previously showed that lncRNA8975-1 was overexpressed in regressive scars compared to mature scar tissue [12].…”
Section: Discussionmentioning
confidence: 99%